Dialogue Summary: Expanding the Uptake of Hospital-based Tobacco-use Cessation Supports Across Ontario - Lavis, JN (My University, 2012)
A summary of what was learned from a stakeholder dialogue that addressed problems related to expanding the uptake of hospital-based tobacco-use cessation supports, options for addressing these problems, key implementation considerations, and next steps for expanding the uptake of hospital-based tobacco-use cessation supports across Ontario.
Keywords: hospital; tobacco; cessation; Ontario